2022
DOI: 10.3390/ijerph191710637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shallow Groundwater Quality at Regional Scales Using Adaptive Water Quality Indices

Abstract: Groundwater, which is the main source of water for human consumption in many rural areas, has its quality determined by the complex interaction of environmental factors and anthropogenic activities. The present study evaluated the quality of shallow groundwater (1 to 25 m depth) in the rural area of the Târgovişte Plain, a densely populated area (200 inhabitants/km2) using 80 water samples collected from public wells. In order to explain the spatial distribution of the concentrations of the 19 physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
0
5
0
6
Order By: Relevance
“…Many studies have used various indices to predict the water quality of different regions for drinking and other uses [18,[21][22][23][24][25][26]. [27] have proposed a simple effective method to summarize the overall characters (physicochemical and biological) of water to produce a simple, stable, consistent, and repeatable index that could be used to assess water quality [28,29].…”
Section: Water Quality Index Wqimentioning
confidence: 99%
“…Many studies have used various indices to predict the water quality of different regions for drinking and other uses [18,[21][22][23][24][25][26]. [27] have proposed a simple effective method to summarize the overall characters (physicochemical and biological) of water to produce a simple, stable, consistent, and repeatable index that could be used to assess water quality [28,29].…”
Section: Water Quality Index Wqimentioning
confidence: 99%
“…It is considered that < 10 -6 is not characterized by negative health effects. The range 10 -6 < < 10 -4 can be considered acceptable under certain conditions, and > 10 -4 have major negative health effects [5,13,[40][41][42][43].…”
Section: Figure 6 the Hazard Quotient (Total And For Each Investigate...mentioning
confidence: 99%
“…Thus, the investigations conducted using GIS combined with hydrochemical methodologies to identify the sources of groundwater pollution are beneficial for monitoring groundwater quality 12 . Numerous studies on using GWQI and GIS for groundwater quality assessment have been reported in the literature [14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%